622 Marketing Communication and Perceived Health Care Quality: antecedents of Physiotherapists’ Job Satisfaction (Balneo and PRM Research Journal, 2024)
The performance of a health care organization is impacted by how its management handles problems caused by disruptions in communication and shows concern for the ongoing enhancement of the communication process. Any health care organization’s marketing communication approach is essential since it has an impact on both personnel and consumer satisfaction. From the perspective of physiotherapists, the current study aims to explore the connections between the perceived quality of health care services, marketing communications and job satisfaction. The sample comprised 114 individuals, the majority of whom were women, and whose average age was 39,74 (±9,56). Their average experience in the health care organization was 12,44 years (± 8,95). A self-administered questionnaire that contained socio-demographic items and specific items to collect data about the importance of marketing communication, job satisfaction, and perceived quality, was used as the research instrument. The results revealed that physiotherapists’ job satisfaction is positively influenced by both marketing communication and the perceived quality of care. However, to be more effective, health care managers need to offer specialized trainings to physiotherapists in order to motivate them and strengthen reliability and responsiveness when providing services. Keywords: marketing communication, quality of care, job satisfaction, medical rehabilitation services, recovery services